(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This article delves into exploring various methods utilized in teaching foreign languages and assesses their effectiveness in promoting language acquisition. The author highlights the significance of selecting appropriate teaching methods to optimize learning outcomes and discusses different approaches that are commonly employed in language classrooms. In today's interconnected world, the importance of learning foreign languages has become increasingly recognized, leading to a growing interest in teaching methodologies that promote effective language acquisition.